Strategi Guru dalam Mengatasi Kekurangan Media Pembelajaran Pada Materi Siklus Air Di Kelas V SD - Deva Merlin Claudia; Khusnul Qotimah; Arum Desta Widyawati; Erwin Efendi Hutagalung; Ayatullah Muhammadin Al Fath (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to describe the strategies employed by fifth-grade teachers in overcoming the lack of learning media for water cycle material in elementary schools located in remote areas. The research employed a qualitative descriptive approach with data collected through observation, semi-structured and unstructured interviews, and documentation techniques. Data sources consisted of fifth-grade teachers and school principals selected through purposive sampling. Data validity was ensured through source triangulation and technique triangulation. Data analysis followed the Miles and Huberman model comprising data reduction, data display, and conclusion drawing. The results revealed that teachers applied four adaptive strategies: (1) creating simple teaching aids from locally available materials, (2) utilizing the surrounding environment as an authentic learning resource, (3) applying discussion and demonstration methods, and (4) optimizing simple digital technology. Supporting factors included teacher creativity and principal support, while barriers encompassed budget constraints, limited professional training, and geographic isolation. This study concludes that teacher creativity and initiative serve as the primary determinants of successful learning amid facility limitations, functioning as practical 'prescriptions' to address the 'disease' of media scarcity.